Compact Vertically-Coupled Microring Laser Array Dual-Wavelength Source for Terahertz Mode Beating - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2007)
Continuous-wave operation of a fully tunable compact microring twin-laser array is demonstrated for the first time. The two active microrings, with radii of 70μm and 74μm, are vertically- coupled to a single passive waveguide. Tuning of the current facilitates a wavelength separation from 4.9nm to 6.3nm.